MRSA-colonized persons' and healthcare personnel's experiences of patient-professional interactions in and responsibilities for infection prevention in Sweden - Maria Lindberg; Marianne Carlsson; Bernice Skytt (Elsevier, 2014)
Summary: Background: Patient-professional interactions and adherence to infection control measures are central to the quality of care and patient safety in healthcare. Persons colonized with methicillin-resistant Staphylococcus aureus (MRSA) describe insufficient support and unprofessional behavior among healthcare personnel. Methods: A descriptive qualitative study was conducted to investigate managers', physicians', registered nurses' and MRSA-colonized persons' experiences of patient-professional interactions in relation to and responsibilities for infection prevention in the care of colonized patients. Five persons with MRSA colonization and 20 healthcare personnel employed within infection, hematology, nephrology or primary healthcare settings participated. The data were collected using open-ended semi-structured individual interviews with the MRSA-colonized persons and semi-structured focus group interviews with the healthcare personnel. Results: The participants perceived MRSA as an indefinable threat and described that the responsibility for infection prevention is important, but such adherence was a neglected and negotiable issue. The described actions that were acknowledged as unprofessional and inappropriate adherence to infection prevention resulted in stigmatized patients. Conclusion: Colonized persons' and healthcare personnel's understanding of MRSA determines whether the personnel's behavior is perceived as proper or improper. Individual responsibility for patient-professional interactions in relation to MRSA colonization and adherence to infection control measures should be more stringent. Keywords: Infection prevention, MRSA, Patient-professional interaction, Responsibility